Os valores e as emoções como fundamentos das decisões judiciais - Tatiana Affonso Ferreira Paiva (2019)
This present research has as its starting point the votes of the Supreme Court reporting ministers in decisions of constitutional actions proposed in order to question, in light of the 1988 Federal Constitution Principles, the expansion of LGBT + community rights. Within this theme, the corpus brings together questions about the recognition of homosexual union, the possibility of blood donation by homosexuals, the criminalization of homophobia, the possibility of name and gender change directly at registry offices and the unconstitutionality of terms which make up the libidinous act crime within the Military Penal Code. From this corpus, we find that judicial decisions are not always based on articles of law or legal arguments, often times, based on extrajudicial elements such as the values that govern social construction. For such an understanding, we approach Perelman & Olbrechts-Tyteca’s ([1958] 2005) New Rhetoric and his Logic of Values as a theoretical framework, since his proposal is precisely to question the epistemological project of Legal Positivism as the only way to think and apply the Law. In this sense, the author proposes that Law cannot be dictated by Formal Logic, but must be taken from the reasonable and essentially rhetorical reasoning. From this perspective, the paper theoretically seeks to understand what values are, how they relate to emotions, and how such elements can underpin court decisions. Therefore, we seek support from axiological authors such as Scheler (2001), Hessen (1980) and Frondizi (1991) and those who have been dedicated to the study of emotions such as Le Breton (2009), Pequeno (2017) and Ribeiro (2017). Recognizing the relationship between values and emotions would be an attempt to advance rhetorical studies, that for a long time, no longer gave the deserved importance to emotions. Regarding the analytical aspect of the work, we seek to verify in light of a rhetorical-discursive analysis, which values became argumentative axes in the decisions that democratized some LGBT+ rights and how these values appeared discursively in this typically argumentative decision-making genre. For this, we highlight the contributions of Classical Rhetoric, New Rhetoric, Discourse Analysis and Argumentative Discourse Analysis, with emphasis on the proposals of Aristoteles (2005), Perelman & Olbrechts-Tyteca’s ([1958] 2005), Amossy (2018), Plantin (2011), e Lima (2006). A reflection on the topic also involves the questions that permeate the LGBT + universe and, finally, the role of the Judiciary Power in the implementation of the principles of the Democratic State of Law, based on theories of argumentation. Keywords: Legal Discourse; Theories of argumentation; Rhetoric; New Rhetoric; Argumentative Analysis of Speech; Values; LGBT